Answer:
11.3 m/s
Step-by-step explanation:
First, find the time it takes for the first stone to fall 3.2 m.
Given:
Δy = 3.2 m
v₀ = 0 m/s
a = 9.8 m/s²
Find: t
Δy = v₀ t + ½ at²
(3.2 m) = (0 m/s) t + ½ (9.8 m/s²) t²
t = 0.81 s
Next, find the time for the first stone to land.
Given:
Δy = 15 m
v₀ = 0 m/s
a = 9.8 m/s²
Find: t
Δy = v₀ t + ½ at²
(15 m) = (0 m/s) t + ½ (9.8 m/s²) t²
t = 1.75 s
The difference in time is 1.75 s − 0.81 s = 0.94 s. Find the initial velocity needed for the second stone to land after that amount of time.
Given:
Δy = 15 m
a = 9.8 m/s²
t = 0.94 s
Find: v₀
Δy = v₀ t + ½ at²
(15 m) = v₀ (0.94 s) + ½ (9.8 m/s²) (0.94 s)²
v₀ = 11.3 m/s